INOVASI LAYANAN PERPUSTAKAAN DI MASA PANDEMI COVID-19 : STUDI KASUS DI PERPUSTAKAAN FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS DIPONEGORO - Endhar Priyo Utomo (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The Covid-19 pandemic outbreak, which was first discovered in China, has now spread in various parts of the world, including Indonesia. To deal with the spread of this epidemic, the government and several Diponegoro Universities issued several regulations that were used to minimize the spread of the Covid-19 virus. The existence of a number of these regulations have an impact on activities that occur in the community and also the activities of learning activities in universities. All activities are shifted from being carried out on campus to at home. This makes the academics of Diponegoro University unable to access information resources in the library. Libraries make some anticipatory steps to overcome this obstacle, namely among them is to optimize the sources of information available and make some innovation services that exist in the library at this time. This is done so that the main purpose of the library to be able to provide satisfaction to users of the services provided can be fulfilled.